Salvia officinalis L. coverage on plants development - C.T.A. CRUZ-SILVA; L.H.P. NÓBREGA; S.M. DELLAGOSTIN; C.F.G. SILVA
ABSTRACT Medicinal plants with essential oils in their composition havetypicallybeen shown to be promising in plant control. Sage (Salvia officinalis L.) is cited for its allelopathic effects. This study evaluated the allelopathic potential of dried sage leaves in vegetation, soil and the development of Lycopersicon esculentum Mill. (tomato), Panicum maximum Jacq. (guinea grass) and Salvia hispanica L. (chia) plants. Three seedlings were transplanted seven days after germination in 1 kg plastic containers with soil, in a greenhouse. The grinded dry mass of sage was placed at rates of 3.75; 7.5 15 t ha-1, and a control (no mass). After 30 days, the chlorophyll index of tomato and guinea grass plants were inhibited with 7.5 and 15 t ha-1 sage cover crops. Tomato shoot length was inhibited in all tested rates, and guinea grass plants showed some reduction in growth when using the highest rate of sage mass (15 t ha-1). The dry mass of tomato and guinea grass plants was reduced when using the15 t ha-1, and 7.5 and 15 t ha-1 of sage cover crops, respectively. It can be concluded that there was some effect of sage coverage on the soil in tomato and guinea grass, but no effect was observed on chia plants.